Association Between Stress Mindset, Work‐Related Stress and Burnout in Nursing Professionals: Empirical Research Quantitative - Fernanda Carini Da Silva; Juliana Nery Souza‐Talarico; Talita Pavarini Borges; Gisele Kuba; Ruth Natalia Teresa Turrini (Nursing Open, 2025)
ABSTRACT Aim To determine the relationship between stress mindset, work‐related stress and burnout in nursing professionals. We hypothesised that a stress‐is‐debilitating mindset is associated with higher work‐related stress and burnout levels. Design Cross‐sectional study. Methods Data from 119 nursing professionals recruited from oncology hospitals were evaluated. We used the Stress Mindset Scale for general and specific stressor conditions, the Work‐Stress Scale and the Maslach Burnout Inventory. Regression analysis adjusted for covariates was applied to assess the association between stress mindset, work stress and burnout. Results A stress‐is‐debilitating mindset in general and specific stressful contexts was linked to higher levels of work‐related stress. However, no significant associations were found with burnout outcomes such as emotional exhaustion, depersonalisation or personal accomplishment. Conclusion These findings suggest that while stress mindsets are related to work‐related stress, their connection to burnout outcomes requires further exploration. Future studies should consider a longitudinal design with a diverse sample of nursing professionals at various career stages. Implications for the Profession The findings highlight the potential value of stress management training tailored to nurses' individual stress mindsets and workplace challenges. Future longitudinal studies and clinical trials are needed to assess whether enhancing stress mindset can reduce work‐related stress and burnout, guiding the development of more effective and personalised interventions to support nurses' mental health and job satisfaction. Impact This study addressed the problem of work‐related stress and burnout among nursing professionals, focusing on how stress mindsets are associated with these outcomes. The main findings revealed that a stress‐is‐debilitating mindset is linked to higher levels of work‐related stress but does not significantly correlate with burnout. By highlighting the importance of stress mindsets, the study suggests that tailored stress management training and clinical trials to enhance stress mindsets could improve mental health and job satisfaction among nurses, ultimately contributing to healthier work environments and better patient care. Reporting Method This article adheres to the STROBE Statement guidelines for reporting cross‐sectional studies, ensuring clarity, transparency and reproducibility of the research findings. Patient or Public Contribution No patient or public contribution.